IMPLEMENTASI KEBIJAKAN REKRUTMEN PEGAWAI PT. PERUSAHAAN LISTRIK NEGARA WILAYAH SULUTTENGGO - Sihombing, Tiorisma; Rorong, Arie; Laloma, Alden (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: Human resources planning that is hard-wired with good will support the quality ofprospective employees as well as the number of types of labour required at any given time, so being able tohelp the recruitment of employees. the process of recruitment of prospective employees who have the abilityto work in a company. PT PLN (Persero) conducts recruitment with several stages of recruitment, i.e.registration of participants, calling on the participants to the process of administration by bringing files thathad been noted at the time of registration, selection of administration, general aptitude test, academic andEnglish, the psychological test, interview and health tests. the environment PT PLN (Persero) is a publiccompany engaged in the service so it has a great responsibility to be able to provide the best service to thecommunity. The company is one of the strategic initiatives prepared for transforming human resources(human capital). to form a quality workforce then need to determine qualifications regarding labor is neededand put it in the right position, so that the company's goals will be achieved. to achieve the objectives of thecompany then needed a good workforce planning for each Division or Department within the company. Theimplementation of the recruitment policy of the State electricity company PT. (Persero) Region Suluttenggo.Views of 6 Implementation according to the theory of van meter and van horn that is standard policy andobjectives, resources, implementing agencies/implementor, implementer of the attitudes, communication,social conditions, economic, political. This research is a descriptive qualitative approach method through indepthinterviews to 8 people additional observations, the informant in the form of a list of guidelines forinterviews and writing stationery. The results showed in general recruitment policy ImplementationEmployees of the State electricity company PT has not gone well.Keyword: Employee Recruitment Policy Implementation